ChemInform Abstract: Syntheses of 5′‐Amino‐2′, 5′‐dideoxy‐2′, 2′‐difluorocytidine Derivatives as Novel Anticancer Nucleoside Analogues. Issue 25 (24th June 2014) - Labroli, Marc A.; Dwyer, Michael P.; Shen, Ruichao; Popovici‐Muller, Janeta; Pu, Qinglin; Richard, Judson; Rosner, Kristen; Paruch, Kamil; Guzi, Timothy J.
Abstract A series of 5′‐amino derivatives of gemcitabine are synthesized in order to identify anticancer nucleoside analogues (no biological activity reported).